Sorbus gongshanensis (Rosaceae), a new species from the Hengduan Mountains, China - Meng Li; Xin-Fen Gao; Jing Tian; Wen-Bin Ju (PhytoKeys, 2020)
Sorbus gongshanensis sp. nov., a new species from the Hengduan Mountains China, is described and illustrated. It is similar to S. kurzii from China (Yunnan & Xizang), Nepal, and Sikkim in the size of the leaflets, glabrous veins, persistent (sometimes) herbaceous stipules and reddish brown villous inflorescences and red fruits, but differs in its serrate leaflet margins toothed in the distal half or often almost to their base, reddish brown villous to glabrous hypanthium and reddish brown villous infructescences, among other characteristics.